Glossary of Vocational and Professional Education and Training - Knutti, Peter [Sonstige] (SDBB Verlag, 2014)
This English glossary contains 231 key terms in the Vocational and Professional Education and Training (VPET) field. It is based on the fourth edition of this reference work in German. The terminology is based on the English versions of federal legislation such as the Federal Vocational and Professional Education and Training Act and its corresponding Ordinance, the Swiss Education Report 2014 and other publications by federal agencies. The glossary is also available as an online version (www.vpet.ch) which allows to switch from English to another language (German, French, Italian). (BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 2.2.1 Westeuropa; Lexikon; Berufsbildung; Schweiz